ECONOMIC VALUATION OF TANAH LOT TOURIST ATTRACTION: TRAVEL COST METHOD AND CONTINGENT VALUATION METHOD - Dian Ayu Rahmadani; I Wayan Priyana Agus Sudharma (International Journal of Applied Science and Sustainable Development (IJASSD), 2020)
This study, entitled "Economic Valuation of Tanah Lot Tourist Attraction: The Travel Cost Method and The Contingent Valuation Method".The objective of the study is to estimate the economic value of Tanah Lot tourist attraction withthe travel cost method and the contingent valuation method based on domestic and foreign tourists.The variables used in this study are the dependent variable (number of visits and willingness to pay) and the independent variable (travel expenses, income, time, quality, and presence or absence attractions substitution).The data used in this study are the primary data that answer of the questionnaire from 100 respondents and the secondary data, data on the number of visitors Tanah Lot tourist attractions. The conclusion of the study is the economic value of Tanah Lot tourist attraction based on the travel cost method is the combination of domestic travelers and foreign tourists were in the range of Rp100.637.045.895.000,00 to Rp590.826.836.085.000,00 with average economic value of Rp294.535.273.042.000,00 and the economic valuation of Tanah Lot tourist attraction based on the contingent valuation method is the combination of domestic and foreign tourists were in the range of Rp52.623.720.045,00 to Rp Rp209.324.845.665,00 with average economic value of Rp122.387.253.768,00.